Penerapan Teknik "Mistake Buster" Sebagai Pendekatan Berbasis Refleksi Diri Efektif dalam Meningkatkan Penguasaan Grammar Bahasa Inggris - Guntur, M (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This report aims to investigate the effectiveness of implementing the "Mistake Buster" technique as a self-reflective-based approach in improving English grammar proficiency among 10th-grade students in Makassar. This study employs a mixed-method design, combining quantitative and qualitative data collection and analysis. The study participants consist of 30 students who underwent a 2-cycle intervention using the "Mistake Buster" technique. This intervention focuses on active student engagement in identifying and rectifying their grammar errors through self-reflection. Students are involved in various activities, such as error analysis, peer feedback, and targeted grammar exercises. Quantitative data were collected through pre and post-tests to measure the level of students' grammar proficiency before and after the intervention. The results indicate a significant improvement in students' grammar scores, demonstrating the effectiveness of the "Mistake Buster" technique in enhancing grammar proficiency. Overall, these findings suggest that the "Mistake Buster" technique, as a self-reflective-based approach, can effectively enhance English grammar proficiency among 10th-grade students. This technique encourages student engagement, self-directed learning, and collaborative problem-solving, enabling students to identify, rectify, and avoid grammar errors more effectively.. Keywords: action research, grammar proficiency, self-reflection, "Mistake Buster" technique, 10th-grade students, English language learning